1986
DOI: 10.1172/jci112436
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant injury of cells. DNA strand-breaks activate polyadenosine diphosphate-ribose polymerase and lead to depletion of nicotinamide adenine dinucleotide.

Abstract: To determine the biochemical basis of the oxidant-induced injury of cells, we have studied early changes after exposure of P388D, Poly-ADP-ribose polymerase, a nuclear enzyme associated with DNA damage and repair, which catalyzes conversion of NAD to nicotinamide and protein-bound poly-ADP-ribose, was activated by exposure of the cells to concentrations of 40 ,uM H202 or higher. Activation of poly-ADP-ribose polymerase was also observed in peripheral lymphocytes incubated in the presence of phorbol myristate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
205
2
6

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(221 citation statements)
references
References 50 publications
8
205
2
6
Order By: Relevance
“…This result justify by Luann et al (2002) who reported that, oxidative DNA damage is associated with intense noise exposure in the rat. One of the possibility is that DNA can be an early target of damage in mammals, such that strand breakage occurs before detectable lipid peroxidation or protein damage (Schraufstatter et al, 1986). The damage may result from direct ROS activity or may be an indirect result of ROS lipid peroxidation.…”
Section: Dna Fragmentationmentioning
confidence: 99%
“…This result justify by Luann et al (2002) who reported that, oxidative DNA damage is associated with intense noise exposure in the rat. One of the possibility is that DNA can be an early target of damage in mammals, such that strand breakage occurs before detectable lipid peroxidation or protein damage (Schraufstatter et al, 1986). The damage may result from direct ROS activity or may be an indirect result of ROS lipid peroxidation.…”
Section: Dna Fragmentationmentioning
confidence: 99%
“…An excessive stimulation of PARP-1 can lead to depletion of NAD + /NADH and can therefore interfere with the synthesis of ATP [76], leading to a state of cytopathic hypoxia and cell death. is has been studied in various cells, including macrophages and smooth muscle cells stimulated with oxidizing molecules [77], and enterocytes stimulated with proin ammatory cytokines and oxidizing molecules [78].…”
Section: Activation Of Enzymes In Ol Ed In Dna Damage Repair: Poly (Amentioning
confidence: 99%
“…oxidative stress [7] and exposure to various mutagens [8] or to UV light [6]. Activation of PADPRP does not occur at the gene level, but through interaction between PADPRP and damaged DNA [9].…”
Section: Poly(adp-ribose)polymerasementioning
confidence: 99%